2021
DOI: 10.1080/13880209.2021.1981399
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Pristimerin inhibits neuronal inflammation and protects cognitive function in mice with sepsis-induced brain injuries by regulating PI3K/Akt signalling

Abstract: Context Sepsis is a systemic inflammatory disease; pristimerin exhibits strong antibacterial, anti-inflammatory and antioxidant properties. Objectives We explored whether pristimerin protected against cognitive dysfunction and neuroinflammation in C57BL/6 J mice with sepsis-induced brain injuries. Materials and methods Sepsis was induced by intraperitoneal administration of 2 mg/kg lipopolysaccharide (LPS). C57BL/6 J mice were separated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Meanwhile, after injuries, Neuronal apoptosis induced by ischaemia-reperfusion is associated with the neuroinflammation 45 , while oxidative stress induced by the injuries could stimulate the neuroinflammatory cascades, including activations of NLRP3 inflammasome and secretion of inflammatory cytokines, IL-1β, IL-18, TNF-α and IL-6 46 . Pro-inflammatory cytokines may further exacerbate neuronal apoptosis resulting in behavioural deficits 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, after injuries, Neuronal apoptosis induced by ischaemia-reperfusion is associated with the neuroinflammation 45 , while oxidative stress induced by the injuries could stimulate the neuroinflammatory cascades, including activations of NLRP3 inflammasome and secretion of inflammatory cytokines, IL-1β, IL-18, TNF-α and IL-6 46 . Pro-inflammatory cytokines may further exacerbate neuronal apoptosis resulting in behavioural deficits 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have suggested that activation of PI3K/AKT signaling could mediate neuronal survival during sepsis. Various biomolecules and pharmaceuticals, such as Chromogranin A-derived peptide CGA47-66, Ghrelin, Pristimerin, and Dexmedetomidine, could attenuate blood-brain barrier (BBB) destruction [ 24 ], brain edema [ 25 ], neuroinflammation [ 25 ], synaptic injury [ 26 ], neuronal apoptosis [ 27 , 28 ]. Thus, PI3K/AKT signaling could represent potential diagnosis markers, therapeutic targets, and prognosis indicators in neural dysfunction during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Pristimerin can ameliorate neuronal injury in septic brain injury mice, mainly by regulating PI3K/Akt signaling pathway (Xue et al, 2021). Tanshinone IIA has a neuroprotective effect on sepsis mice, and in addition to its anti-inflammatory effects, its mechanism may be related to inhibiting the activation of astrocytes and microglia (Xiong et al, 2019).…”
Section: Single Ingredientsmentioning
confidence: 99%